2020
DOI: 10.1161/jaha.119.015304
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion After Stage I Palliation Is Associated With Worse Clinical Outcomes

Abstract: Background Packed red blood cell transfusion may improve oxygen content in single‐ventricle neonates, but its effect on clinical outcomes after Stage 1 palliation is unknown. Methods and Results Retrospective multicenter analysis of packed red blood cell transfusion exposures in neonates after Stage 1 palliation, excluding those with intraoperative mortality or need for extracorporeal membrane oxygenation. Transfusion practice variability was assessed, and multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Our results are consistent with many other studies in which the negative effects of transfusion have been proven [ 45 ]. However, it should be taken into account that in our research, only the strategy of managing patients with septal congenital heart disease was studied.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with many other studies in which the negative effects of transfusion have been proven [ 45 ]. However, it should be taken into account that in our research, only the strategy of managing patients with septal congenital heart disease was studied.…”
Section: Discussionsupporting
confidence: 94%
“…Cardiac surgery and the attendant myocardial ischemia reperfusion injury damage the coronary endothelium, impairing NO production and contributing to a decrease in NO bioavailability ( 9 ). Following the NP, the immature neonatal myocardium is particularly vulnerable to cardiac ischemia due to multiple factors including obligate cyanosis; increased cardiac demand due to the inefficiency of the parallel circulation and requirement for an elevated cardiac output; obligate retrograde aortic flow to coronary arteries arising from a diminutive, native ascending aorta; and in those undergoing the Blalock-Taussig shunt (BTS), diastolic hypotension and “coronary steal” resulting from diastolic “run-off” into the pulmonary circulation ( 3 , 11 , 16 ).…”
mentioning
confidence: 99%
“…Firm conclusions about packed red blood cell transfusions in the management of patients with parallel circulation cannot be made from the current data. Other studies have demonstrated con icting ndings [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 95%